Effect of Different Surface Treatments on the Shear Bond Strength of Metal Orthodontic Brackets Bonded to CAD/CAM Provisional Crowns - Dany Haber; Elie Khoury; Joseph Ghoubril; Nunzio Cirulli (MDPI AG, 2023)
Background: The aim of this study was to find the best surface treatment for CAD/CAM provisional crowns allowing the optimal bond strength of metal brackets. Methods: The sample consists of 30 lower bicuspids and 180 provisional crowns. The provisional crowns were randomly divided into six different groups. Orthophosphoric acid etching (37%) was applied to 30 lower bicuspids. The provisional crowns had undergone different surface treatments. Group 1: No treatment (Control Group). Group 2: Diamond bur. Group 3: Sandblasting. Group 4: Plastic Conditioner. Group 5: Diamond bur and Plastic Conditioner. Group 6: Sandblasting and Plastic Conditioner. The brackets in all groups were identically placed using Transbond XT® Primer and Transbond XT® Paste. Then, the entire sample underwent an artificial aging procedure, and a measurement of the bond strength was conducted. After debonding, the surface of the crowns was examined to determine the quantity of the adhesive remnant. Results: Bonding to natural crowns recorded the highest average, followed by the averages of groups 5 and 6. However, group 1 recorded the lowest average. Groups 2 and 4 had very close averages, as well as groups 5 and 6. A statistically significant difference between the averages of all groups was recorded (p < 0.001) except for groups 2 and 4 (p = 0.965) on the one hand, and groups 5 and 6 (p = 0.941) on the other hand. Discussion: The bonding of brackets on provisional crowns is considered a delicate clinical procedure. In fact, unlike natural crowns, the orthophosphoric acid usually used does not have any effect on the surface of provisional crowns. Conclusions: Using a diamond bur combined with the plastic conditioner and sandblasting combined with that same product resulted in a bond strength close to natural crown.